2010
DOI: 10.4013/nbc.2010.52.08
|View full text |Cite
|
Sign up to set email alerts
|

Potencial dos óleos essenciais de plantas no controle de insetos e microrganismos

Abstract: ResumoAs substâncias repelentes ou atraentes das plantas são, principalmente, de natureza terpênica e se apresentam como moléculas de baixo peso molecular e volátil. Essas substâncias, normalmente, são conhecidas como aromáticas e se denominam óleos essenciais, os quais se acumulam em todos os órgãos vegetais. Nos vegetais, os óleos essenciais desenvolvem funções relacionadas com sua volatilidade, agindo na atração de polinizadores, na proteção contra predadores, nos patógenos, na perda de água, no aumento de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
12

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 22 publications
0
24
0
12
Order By: Relevance
“…The results of Knaak and Fiuza (2010) showed that the production of essential oil is viable and profitable. However, to obtain high quality products that are competitive in the market, incentives are necessary to develop modern techniques of cultivation, selection and plant breeding.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The results of Knaak and Fiuza (2010) showed that the production of essential oil is viable and profitable. However, to obtain high quality products that are competitive in the market, incentives are necessary to develop modern techniques of cultivation, selection and plant breeding.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, it is necessary to conduct insightful research on the chemical composition of plant-derived substances and their effects. The process of extracting solvents, the applications of the techniques in the field, conservation and plant selectivity also need to be further evaluated (KNAAK;FIUZA, 2010) Essential oils are distributed in a limited number of families, such as Asteraceae, and accumulate in all types of plant vegetative organs such as the flowers, leaves, barks, roots, rhizomes, fruits and seeds. In most cases, the biological function of the essential oil terpenoids remains obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the mechanism of action of essential oils and its constituents is unknown, the appearance of toxic signs is fast (KNAAK & FIUZA, 2010). Any of these observations could explain the differences in development time and mortality of M. domestica treated with pure citral and citral found in the essential oil diluted in DMSO.…”
Section: Bioassaysmentioning
confidence: 99%
“…The insecticidal action of essential oils can occur in different ways and may cause mortality, deformities at different stages of development, repellency, and deterrence. Through the contact, essential oils can interact with the tegument of insects, besides acting in digestive and neurological enzymes (Isman, 2006;Knaak and Fiuza, 2010).…”
Section: Treatment (Extracts)mentioning
confidence: 99%